2006
DOI: 10.1128/jb.188.7.2454-2462.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxyR in the Oral Anaerobe Porphyromonas gingivalis

Abstract: Porphyromonas gingivalis is an anaerobic microorganism that inhabits the oral cavity, where oxidative stress represents a constant challenge. A putative transcriptional regulator associated with oxidative stress, an oxyR homologue, is known from the P. gingivalis W83 genome sequence. We used microarrays to characterize the response of P. gingivalis to H 2 O 2 and examine the role of oxyR in the regulation of this response. Most organisms in which oxyR has been investigated are facultative anaerobes or aerobes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 51 publications
2
116
1
Order By: Relevance
“…This might be explained by cross-talk in their regulatory pathways, as it has been established in several organisms that sodB is regulated by Fur (Thompson et al, 2002;Fee, 1991;Ernst et al, 2005) and oxyR (Diaz et al, 2006). These transcriptomic observations implicate the involvement of global transcriptional regulators in the control of this adaptation, which might indicate the existence of a stochastic fluctuation in gene expression levels that gives rise to these subtypes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This might be explained by cross-talk in their regulatory pathways, as it has been established in several organisms that sodB is regulated by Fur (Thompson et al, 2002;Fee, 1991;Ernst et al, 2005) and oxyR (Diaz et al, 2006). These transcriptomic observations implicate the involvement of global transcriptional regulators in the control of this adaptation, which might indicate the existence of a stochastic fluctuation in gene expression levels that gives rise to these subtypes.…”
Section: Discussionmentioning
confidence: 98%
“…The OxyR (PG0270) protein is known to regulate several oxidative stress genes in P. gingivalis (Diaz & Rogers, 2004;Diaz et al, 2006), and although they were not present in our signature set, a selection were regulated in the invasive/ non-invasive and protease strains, including ahpC (alkylhydroperoxidase, PG0430) and uspA (oxidative stress resistance, PG0245), which are known to be key genes for stress resistance in P. gingivalis (Ueshima et al, 2003;Johnson et al, 2004;Chen et al, 2006). These data indicate that the invasive subtypes are likely to be well adapted to their intracellular environment, and indeed we found that they retained greater viability after exposure to hydrogen peroxide (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis of P. gingivalis in the presence of hydrogen peroxide has further extended our understanding of the complex response of this organism to oxidative stress (8,46,184). Diaz,et al (46) in their DNA microarray analysis of P. gingivalis isogenic mutants, have demonstrated that common OxyR-regulated genes such as dps and ahpFC were not positively regulated in response to H 2 O 2, although, their expression was dependent on the presence of a functional OxyR protein.…”
Section: 3mentioning
confidence: 99%
“…In P. gingivalis, oxidative stress was found to modulate the expression of several proteins including HtpG, GroEL, DnaK, AhpC, FeoB2, TPR domain protein, and trigger factor (8,46,77,82,101,149,184). Since several of these proteins are also involved in heat shock, it implies that the organism uses a multifunctional approach that may involve the gingipains to maintain cell viability under adverse environmental conditions.…”
Section: 3mentioning
confidence: 99%
“…Oxidative stress defence is an important cellular protective mechanism(s) which plays a crucial role in the survival of all bacteria especially anaerobic bacteria (Brioukhanov & Netrusov, 2004) such as P. gingivalis (Henry et al, 2012;Diaz et al, 2006). In the periodontal pocket, the presence of periodontal pathogens including P. gingivalis triggers a massive host immune response including the release of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ) and superoxide (O neutrophils and macrophages (Chapple, 1996).…”
Section: Introductionmentioning
confidence: 99%